(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Hypertensive patients who are not adhering to treatment cannot control their blood pressure so it is important to find solutions that can stabilize blood pressure with food that is consumed and can be found anytime around them. Objective: This study was to identify the effectiveness of cucumber and Ambon banana fruit in reducing blood pressure in hypertensive sufferers. Method: This type of research is a Quasy Experiment with a non-randomized pretest and posttest control group design. Population of this study were hypertensive patient in Pallangga subdistrict and Sample participated were 24 people with hypertension selected by purpossive sampling with the sample formula of unpaired numerical analytic research. Results: There were differences before and after treatment in the two groups, there was no difference in the effectiveness of the sample in the two same treatments. Conclusion: Cucumber and banana fruit are effective for lowering blood pressure.